An Inhibitory Medial Preoptic Circuit Mediates Innate Exploration - Ryoo, Jia; Park, Seahyung; Kim, Daesoo (Frontiers in Neuroscience, 2021)
Animals have an innate motivation to explore objects and environments with unknown values. To this end, they need to activate neural pathways that enable exploration. Here, we reveal that photostimulation of a subset of medial preoptic area (MPA) neurons expressing the vesicular-GABA transporter gene (vgat+) and sending axonal projections to the ventrolateral periaqueductal grey (vPAG) increase exploration in a chamber but cause no place preference when tested there without photostimulation. Photoinhibition of MPAvgat–vPAG projections lead to no emotional changes as measured by normal activity in an open field assay. Electrophysiological recordings revealed that most GABAergic vPAG neurons are inhibited by MPAvgat neurons. In contrast to a previous report that suggested that MPAvgat–vPAG neurons may impart positive valence to induce place preference, our results suggest that these neurons can increase innate exploration.